Female scent signals enhance the resistance of male mice to influenza. - Ekaterina A Litvinova; Elena P Goncharova; Alla M Zaydman; Marina A Zenkova; Mikhail P Moshkin (PLoS ONE, 2010)
The scent from receptive female mice functions as a signal, which stimulates male mice to search for potential mating partners. This searching behavior is coupled with infection risk due to sniffing both scent marks as well as nasal and anogenital areas of females, which harbor bacteria and viruses. Consideration of host evolution under unavoidable parasitic pressures, including helminthes, bacteria, viruses, etc., predicts adaptations that help protect hosts against the parasites associated with mating.We propose that the perception of female signals by BALB/c male mice leads to adaptive redistribution of the immune defense directed to protection against respiratory infection risks. Our results demonstrate migration of macrophages and neutrophils to the upper airways upon exposure to female odor stimuli, which results in an increased resistance of the males to experimental influenza virus infection. This moderate leukocyte intervention had no negative effect on the aerobic performance in male mice.Our data provide the first demonstration of the adaptive immunological response to female odor stimuli through induction of nonspecific immune responses in the upper respiratory tract.